2006
DOI: 10.1111/j.1399-0039.2006.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of killer cell immunoglobulin‐like receptors genotypes in the Lebanese population

Abstract: This study represents the first report on the distribution of 16 Killer cell Immunoglobulin-like Receptors (KIR) genes in 120 unrelated healthy Lebanese individuals. We observed that 2DL2 frequency (61%) comes second highest after South Asians (64%) and 2DL5 frequency (58.3%) is the second highest reported so far after the South Asians (74%). Interestingly, a large number of AA1 genotype individuals with no loci for activating KIR and three completely new BB profiles not previously reported were found in our p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
4
24
0
1
Order By: Relevance
“…The genotype classified as 34 was characterized by the lack of KIR2DL2, KIR2DL3, and KIR2DS5. The absence of KIR2DL2 and KIR2DL3 has been reported previously [29,30,37], although some studies indicated that KIR2DL2/3 are alleles of the same locus [8,15,44] and that KIRs for HLA-C1 are found in all individuals [22,44]. The genotype classified as 37 lacks KIR2DP1 and KIR2DS3.…”
Section: Discussionmentioning
confidence: 94%
“…The genotype classified as 34 was characterized by the lack of KIR2DL2, KIR2DL3, and KIR2DS5. The absence of KIR2DL2 and KIR2DL3 has been reported previously [29,30,37], although some studies indicated that KIR2DL2/3 are alleles of the same locus [8,15,44] and that KIRs for HLA-C1 are found in all individuals [22,44]. The genotype classified as 37 lacks KIR2DP1 and KIR2DS3.…”
Section: Discussionmentioning
confidence: 94%
“…We report here genetic distances of 14 KIR genes for 33 populations, deposited in the Allele Frequencies database (http://allelefrequencies.net) [23] or published [50,[52][53][54][55][56][57], and they group in several clusters. Populations from Oman, Lebanon, Belgium, Spain Guadeloupe, Senegal, and South Africa Xhosa are in the same cluster on the bottom of the tree.…”
Section: Discussionmentioning
confidence: 99%
“…A hierarchical cluster was conducted based on allelic frequencies of the same 14 KIRs of our observed population and other previously published populations [26,31,32,35,36,38,39,44,[50][51][52], and a neighborjoining tree was constructed using SPSS 13.0 software. The result is shown in Figure 1.…”
Section: Discussionmentioning
confidence: 99%